Ultrafast switching of hard X‐rays. (24th January 2014) - Gaal, Peter; Schick, Daniel; Herzog, Marc; Bojahr, André; Shayduk, Roman; Goldshteyn, Jevgeni; Leitenberger, Wolfram; Vrejoiu, Ionela; Khakhulin, Dmitry; Wulff, Michael; Bargheer, Matias
<x xml:space="preserve">Abstract</x> A new concept for shortening hard X‐ray pulses emitted from a third‐generation synchrotron source down to few picoseconds is presented. The device, called the PicoSwitch, exploits the dynamics of coherent acoustic phonons in a photo‐excited thin film. A characterization of the structure demonstrates switching times of ≤ 5 ps and a peak reflectivity of ∼10−3. The device is tested in a real synchrotron‐based pump–probe experiment and reveals features of coherent phonon propagation in a second thin film sample, thus demonstrating the potential to significantly improve the temporal resolution at existing synchrotron facilities.